Immunopolarization-regulated 3D printed-electrospun fibrous scaffolds for bone regeneration. (September 2021) - Liu, Xingzhi; Chen, Mimi; Luo, Junchao; Zhao, Huan; Zhou, Xichao; Gu, Qiaoli; Yang, Huilin; Zhu, Xuesong; Cui, Wenguo; Shi, Qin
Abstract: Three-dimension (3D)-printed bioscaffolds are precise and personalized for bone regeneration. However, customized 3D scaffolds may activate the immune response in vivo and consequently impede bone formation. In this study, with layer-by-layer deposition and electrospinning technology to control the physical structure, 3D-printed PCL scaffolds with PLLA electrospun microfibrous (3D-M-EF) and nanofibrous (3D-N-EF) composites were constructed, and their immunomodulatory effect and the subsequent osteogenic effects were explored. Compared to 3D-N-EF scaffolds, 3D-M-EF scaffolds polarized more RAW264.7 cells toward alternatively activated macrophages (M2), as demonstrated by increased M2 and deceased classically activated macrophage (M1) phenotypic marker expression in the cells. In addition, the 3D-M-EF scaffolds shifted RAW264.7 cells to the M2 phenotype through PI3K/AKT signaling and enhanced VEGF and BMP-2 expression. Conditional medium from the RAW264.7 cells seeded in 3D-M-EF scaffolds promoted osteogenesis of MC3T3-E1 cells. Furthermore, in vivo study of repairing rat calvarial defects, the 3D-M-EF scaffolds increased the polarization of M2 macrophages, enhanced angiogenesis, and accelerated new bone formation. Collectively, our data suggested that well-designed 3D-M-EF scaffolds are favorable for osteogenesis through regulation of M2 polarization. Therefore, it is potential to utilize the physical structure of 3D-printed scaffolds to manipulate the osteoimmune environment to promote bone regeneration.